Recent Approaches of Gastroretentive Drug Delivery System – A Review - Jeganath, Dr. S. (Asian Journal of Pharmaceutics (AJP), 2022)
The most effective and approved drug delivery method was the oral route. Due to the enormous therapeutic advantages of orally controlled release dosage forms, enhanced medicinal benefits are favored as the important perspective in the pharmaceutical field. Gastroretentive drug delivery system (GRDDS) is an innovative drug delivery method that has an advantage due to its ability to keep extended stomach retention and thus improve drug stomach residence time and also enhance drug bioavailability. Many technological methods, such as swelling and expansion, mucoadhesive, high density, ion exchange, raft forming, magnetic, and floating drug delivery systems, are used to prolong gastric residence time. The objective of this analysis on GRDDSs was to assemble of different gastroretentive approaches that are previously leading methods in the field orally administered controlled release drug delivery.